2016
DOI: 10.1542/peds.2015-0709
|View full text |Cite
|
Sign up to set email alerts
|

Early-Onset Scoliosis: A Review of History, Current Treatment, and Future Directions

Abstract: Early-onset scoliosis (EOS) is defined as curvature of the spine in children >10° with onset before age 10 years. Young children with EOS are at risk for impaired pulmonary function because of the high risk of progressive spinal deformity and thoracic constraints during a critical time of lung development. The treatment of EOS is very challenging because the population is inhomogeneous, often medically complex, and often needs multiple surgeries. In the past, early spinal fusion was performed in childre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
127
0
7

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 140 publications
(166 citation statements)
references
References 63 publications
(59 reference statements)
2
127
0
7
Order By: Relevance
“…In males, height growth surges at a mean age of 11 years and reaches a PHV of about 9.5 cm/year at the mean age of 13.5 years [53]. EOS (except small curve infantile idiopathic types) has therefore traditionally a worse prognosis, since patients have to go through most of the remaining growth [56]. Progression of congenital curves depends largely on the specific type of defect, but even with stable vertebral defects at skeletal maturity, deterioration of secondary or tertiary curves may lead to considerable increased deformity later in life [58].…”
Section: Progressionmentioning
confidence: 99%
“…In males, height growth surges at a mean age of 11 years and reaches a PHV of about 9.5 cm/year at the mean age of 13.5 years [53]. EOS (except small curve infantile idiopathic types) has therefore traditionally a worse prognosis, since patients have to go through most of the remaining growth [56]. Progression of congenital curves depends largely on the specific type of defect, but even with stable vertebral defects at skeletal maturity, deterioration of secondary or tertiary curves may lead to considerable increased deformity later in life [58].…”
Section: Progressionmentioning
confidence: 99%
“…According to the Scoliosis Research Society, early-onset idiopathic scoliosis (EOIS) is a three-dimensional deformity of the spine that starts before 10 years of age. Severe deformities can affect growth of the rib cage and lead to a decrease in pulmonary volume and to the development of a restrictive respiratory syndrome [1,2].…”
Section: Introductionmentioning
confidence: 99%
“…Pulmonary, cardiovascular and neurological comorbidities are common and in some children there is a 50% higher risk of premature death before the age of 40, with cases as young as 16 years of age being observed (Cheung, Samartzis, & Cheung, ; Pehrsson, Larsson, Oden, & Nachemson, ). The true prevalence of EOS is unknown; however Yang, Andras, Redding, and Skaggs () reported that idiopathic EOS accounted for less than 1% of all scoliosis cases. Indeed, parenting a child with EOS is complex with potential for higher parental burden compared to that of parents of children with asthma, epilepsy, heart disease or cancer (Corona, Matsumoto, Roye, & Vitale, ).…”
Section: Introductionmentioning
confidence: 99%